The investigation of FOG output signal dependency on environment temperature at high rates of temperature change. Issue 1 (May 2021) - Nikiforovskii, Danila; Smirnov, Daniil; Deyneka, Ivan; Nikitenko, Alexander; Rupasov, Andrey
Abstract: The development of fiber-optic and electronic components has led to a significant widening of their application scope, in particular in the construction of ground vehicles navigation systems. Often, such systems have the special performance requirements under difficult temperature conditions: the environment temperature changing rate in some cases may reach several °C/min. One of the key elements of a navigation system is a fiber-optic gyroscope (FOG). The harsh environmental conditions increase the demands on production technology of the FOG, on the choice of construction materials, on the arrangement and shape of the parts, etc., however, in order to decrease temperature effects influence on the output signal of the device, the use of special algorithmic compensation methods is also required. Algorithmic compensation requires careful preparation of input data, which is associated with extensive experimental work. This article analyses the FOG temperature dependence characteristics in the wake of the designated experimental preparation for algorithmic compensation.